Situating Programming Abstractions in a Constructionist Video Game - Weintrop, David; Wilensky, Uri (Informatics in education, 2014)
Research on the effectiveness of introductory programming environments often relies on post-test measures and attitudinal surveys to support its claims; but such instruments lack the ability to identify any explanatory mechanisms that can account for the results. This paper reports on a study designed to address this issue. Using Noss and Hoyles’ constructs of webbing and situated abstractions, we analyze programming novices playing a program-to-play constructionist video game to identify how features of introductory programming languages, the environments in which they are situated, and the challenges learners work to accomplish, collectively affect novices’ emerging understanding of programming concepts. Our analysis shows that novices develop the ability to use programming concepts by building on the suite of resources provided as they interact with the computational context of the learning environment. In taking this approach, we contribute to computer science education design literature by advancing our understanding of the relationship between rich, complex introductory programming environments and the learning experiences they promote.